EDUCAÇÃO E RELAÇÕES DE GÊNERO: ENTRE AVANÇOS E DESAFIOS NA EXPERIÊNCIA DA ESCOLA LATINO AMERICANA DE AGROECOLOGIA - Miranda, Tereza Lopes (2011)
This research addresses issues of gender and the environment in relation to education in the process of forming technologist of the Latin American School of Agroecology, located in the municipality of Lapa in the state of Parana.It has as problematic to verify how the school has organized the questions with regard to education and environment, with emphasis on gender relations. The methodology used is qualitative research, using interviews, field observations, literature and documentary. As goals contextualizes the school, examines the perception of teachers about the gender issue and points to advances and challenges from the practices in the everyday of it. The interviewees are educators members of the teaching staff. As a result the research points to significant advances, such as the school's concern to ensure women's participation in the course. As well as ensuring that gender issues be discussed in the spaces of formation, but mainly in how the school structures the working relationship that directly reflects the change of habits and customs of individuals, causing them to rethink values and behaviors from practices and experiences that guide the teaching of the school. It remains a great challenge to ensure that women reach 50% participation, since they are still a minority, what difficult the organization of work teams in relation to equal participation.